Heavy metal exposures on freshwater snail Pomacea insularum: understanding its biomonitoring potentials - Yap, Chee Kong; Pang, Bin Huan; Cheng, Wan Hee; Kumar, Krishnan; Avtar, Ram; Okamura, Hideo; Horie, Yoshifumi; Sharifinia, Moslem; Keshavarzifard, Mehrzad; Ong, Meng Chuan; Naji, Abolfazl; Ismail, Mohamad Saupi; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The present investigation focused on the toxicity test of cadmium (Cd), copper (Cu), nickel (Ni), lead (Pb) and zinc (Zn), utilizing two groups of juvenile and adult apple snail Pomacea insularum (Gastropod, Thiaridae) with mortality as the endpoint. For the adult snails, the median lethal concentrations (LC50) values based on 48 and 72 h decreased in the following order: Cu < Ni < Pb < Cd < Zn. For the juvenile snails, the LC50 values based on 48 and 72 h decreased in the following order: Cu < Cd < Ni < Pb < Zn. The mussel was more susceptible to Cu than the other four metal exposures, although the juveniles were more sensitive than the adults because the former had lower LC50 values than the latter. This study provided essential baseline information for the five metal toxicities using P. insularum as a test organism, allowing comparisons of the acute sensitivity in this species to the five metals. In conclusion, the present study demonstrated that P. insularum was a sensitive biomonitor and model organism to assess heavy metal risk factors for severe heavy metal toxicities. A comparison of the LC50 values of these metals for this species with those for other freshwater gastropods revealed that P. insularum was equally sensitive to metals. Therefore, P. insularum can be recommended as a good biomonitor for the five metals in freshwater ecosystems.